PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION KARYAWAN STUDI PADA PT. BANK PERKREDITAN RAKYAT MITRATAMA ARTHABUANA - Abdurrahim Abdurrahim; Hastin Umi Anisah; Maya Sari Dewi (Islamic University of Kalimantan MAB Banjarmasin, 2017)
This study aimed to identify and analyze the influence of Job Satisfaction (X1) and Organizational Commitment (X2) as independent variable either simultaneously or individually to Turnover Intention (Y) as the dependent variable at Employee at PT. BPR Mitratama Arthabuana Kertak Hanyar. This was an explanatory research. Multiple linear regression statistical technique were used to analysze the effect Job Satisfaction variable (X1) and Organizational Commitment (X2) on Turnover Intention (Y). Furthermore, to test the level of significance, the F test and t test is with SPSS. The study concluded that two independent variables simultaneously, namely job satisfacation variables (X1) and Organizational Commitment (X2) have significant relationship to Turnover Intention (Y) variable. Meanwhile, individually, Job Satisfaction variable (X1) have significant negative relationship to Turnover Intention (Y), as well as the Organizational Commitment variable (X2) on a Turnover Intention (Y). Keywords : Job Satisfaction, Organizational Commitment, Turnover Intention